Psychological health professionals’ perspectives on Melukat as a cultural approach to psychological therapy - Pristiyanti, Della Cindy; Yuwanto, Listyo (UIN Maulana Malik Ibrahim Malang, 2025)
This study explores the perspective of healthcare professionals in psychology toward the practice of melukat as a culturally based psychological therapy in Bali. Using a qualitative approach, in-depth interviews were conducted with three psychologists experienced in both clinical and traditional practices. The findings indicate that melukat is perceived as an effective religious coping strategy for calming the mind, fostering self-reflection, and supporting relaxation, particularly for individuals who believe in the ritual. However, the practice is not regarded as a primary psychological therapy, as it does not meet the standards of a structured therapeutic process. The integration of melukat into modern therapy is considered promising, especially when combined with psychological techniques such as mindfulness and meditation. The participants emphasized the importance of further research to assess the effectiveness of melukat within the context of modern psychology and the need for collaboration between psychologists and traditional leaders to develop a holistic, culturally sensitive approach. These findings provide new insights for developing more inclusive therapeutic models, integrating traditional practices with scientific methods, and addressing cultural sensitivity challenges in mental health services.